Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5424/fs/2015241-05521
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of fine root length density for six artificial afforestation tree species in Loess Plateau of Northwest China

Abstract: Aim of the study: Data about the distribution of fine root length density (FRLD) is important to understand the ecophysiology of vegetation. This is particularly true when models are applied to describe ecohydrology and vegetation function. However, there is yet limited knowledge of root distributions in semi-arid regions. The aim of this study is to investigate the distribution of fine roots for six typical afforestation tree species in Loess Plateau and its relationships with soil environmental factors.Area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
1
6
1
Order By: Relevance
“…pseudoacacia (Jian et al, 2015). For this reason, A. sibirica in Mspa derived a higher proportion of shallow soil water (60.96%) than R. pseudoacacia in Mspa (43.72%) during the growing seasons.…”
Section: Water Source Partitioning In the Mixed Plantationmentioning
confidence: 97%
See 1 more Smart Citation
“…pseudoacacia (Jian et al, 2015). For this reason, A. sibirica in Mspa derived a higher proportion of shallow soil water (60.96%) than R. pseudoacacia in Mspa (43.72%) during the growing seasons.…”
Section: Water Source Partitioning In the Mixed Plantationmentioning
confidence: 97%
“…These findings imply that A. sibirica and R. pseudoacacia in the different plantation types exhibited distinct water use characteristics. This discrepancy may be attributed to their different ecophysiological characteristics, such as different lateral root distributions (Jian et al, 2015), specific leaf areas (Yan et al, 2010), plasticity of minimum leaf water potential (Miyazawa et al, 2018), and osmotic adjustment ability (Yan et al, 2013). In the same catchment, Wei et al (2018) reported that R. pseudoacacia was negatively affected by water stress but A. sibirica was not by comparing inter-annual radial growth responses to climate change using tree-ring samples in the same catchment.…”
Section: Water Use Characteristics In the Different Plantation Typesmentioning
confidence: 99%
“…The LAI of the trees in the three plots was 2.65±0.31 (mean±SD), tree height was 10.15±3.64 m (mean±SD), and diameter at breast height (DBH) was 20.3±3.7 cm (mean ±SD). The root distribution of P. tabulaeformis was shallow (Jian et al, 2015), more than 90% of the roots was concentrated in the 0-100 cm soil depth.…”
Section: Sap Flow Measurementsmentioning
confidence: 96%
“…Although fine tree roots account for less than 2% of tree biomass, they can contribute to 75% of primary production in mature forests annually, making them important for forest carbon, nutrient, and water cycling processes (Gill andJackson 2000, Brunner and. Fine roots are concentrated on the soil surface and decrease steadily with increasing soil depth (Macinnis-Ng et al 2010, Jian et al 2015. Studies performed in the plantations of six tree species established on agricultural land have shown that the highest fine root density was concentrated at a depth of 0-40 cm (Jian et al 2015).…”
Section: Vegetation Response To Deep Ploughingmentioning
confidence: 99%
“…Fine roots are concentrated on the soil surface and decrease steadily with increasing soil depth (Macinnis-Ng et al 2010, Jian et al 2015. Studies performed in the plantations of six tree species established on agricultural land have shown that the highest fine root density was concentrated at a depth of 0-40 cm (Jian et al 2015). Otherwise, fine roots are known to develop very plastically in response to changing environmental conditions (Meier and Leuschner 2008).…”
Section: Vegetation Response To Deep Ploughingmentioning
confidence: 99%